2014
DOI: 10.5897/ajar2013.8383
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen use efficiency by selected NERICA varieties in Burkina Faso

Abstract: A field experiment was carried out in the 2005 and 2006 wet seasons in Bagré, Burkina Faso, to assess the differences in paddy yield and nitrogen (N) utilization of the New Rice for Africa (NERICA) lowland varieties. The test consists of a split-plot design with four replications. The main plots were represented by four NERICAs (NERICA L 41, NERICA L 60, NERICA L 20, and NERICA L 19) and one control (4418). Subplots were constituted with five rates of nitrogen fertilizer (0, 40, 80, 120 and 160 kg N ha-1). Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Therefore, mineralisation of organic carbon is proportional to the organic matter content of the soil. It has been shown that the fine soil fraction is prone to the mineralisation processes [32]. Similar observations were made in Farako-ba under upland rice growing condition, with sandy silty texture soil.…”
Section: Treatment-induced Effects On Carbon Mineralisationsupporting
confidence: 74%
“…Therefore, mineralisation of organic carbon is proportional to the organic matter content of the soil. It has been shown that the fine soil fraction is prone to the mineralisation processes [32]. Similar observations were made in Farako-ba under upland rice growing condition, with sandy silty texture soil.…”
Section: Treatment-induced Effects On Carbon Mineralisationsupporting
confidence: 74%
“…These management practices include watering regimes, spacing, and soil fertility management. [7] reported significant differences in yield and uptake of nitrogen by paddy rice varieties when they subjected the varieties to different levels of nitrogen fertilizer. Correlations between yield and yield-related traits were shown to vary under different nutrient conditions [8].…”
Section: Introductionmentioning
confidence: 99%